Cattle, Culture, and Calculations: a Logistic Regression Analysis of Livestock Selling Decisions in Deli Serdang, Indonesia - Anggraini, Silvia; Supriana, Tavi; Tafsin, Ma’ruf (Baileo: Jurnal Sosial Humaniora, 2025)
This study examines the factors influencing farmers’ decisions to sell beef cattle in Deli Serdang Regency, Indonesia, using a logistic regression approach. The research was conducted in two sub-districts—Pancur Batu and Hamparan Perak—between November 2024 and January 2025. A purposive sampling method was used to define the target population, while snowball sampling recruited 40 respondents, beginning with four initial informants. Both qualitative insights and quantitative logit modeling were employed to analyze the data. Findings indicate that six independent variables collectively explain 42% of the variance in selling decisions. Partially, perceived cattle prices and religious festive moments significantly influence sales behavior. Higher price perception increases the likelihood of selling, whereas factors such as cattle quality, household needs, and herd size tend to discourage it—highlighting the role of livestock as both economic buffer and cultural asset. This study contributes novel insights by integrating cultural values with economic rationality in modeling farmers’ decision-making. It underscores the importance of recognizing localized socio-economic dimensions in shaping agrarian policy, livestock trade strategies, and evidence-based rural development programs. The study recommends that future research on rural economic behavior explicitly incorporate cultural variables as critical determinants in agricultural decision-making processes.